The moonlighting function of bacteriophage P4 capsid protein, Psu, as a transcription antiterminator - Ranjan, Amitabh (Landes Bioscience, 2013)
Psu, a 20-kD bacteriophage P4 capsid decorating protein moonlights as a transcription antiterminator of the Rho-dependent termination. Psu forms specific complex with E.coli Rho protein, and affects the latter's ATP-dependent translocase activity along the nascent RNA. It forms a unique knotted dimer to take a V-shaped structure. The C-terminal helix of Psu makes specific contacts with a disordered region of Rho, encompassing the residues 139–153. An energy minimized structural model of the Rho–Psu complex reveals that the V-shaped Psu dimer forms a lid over the central channel of the Rho hexamer. This configuration of Psu causes a mechanical impediment to the translocase activity of Rho. The knowledge of structural and mechanistic basis of inhibition of Rho action by Psu may help to design peptide inhibitors for the conserved Rho-dependent transcription termination process of bacteria.